107k views
4 votes
What is the correct solution to the equation 1 – (2x + 4) = –4x + 5?

User Artkoenig
by
4.7k points

2 Answers

5 votes


\\ \sf\longmapsto 1-(2x+4)=-4x+5


\\ \sf\longmapsto 1-2x-4=-4x+5


\\ \sf\longmapsto -2x-3=-4x+5


\\ \sf\longmapsto -2x+4x=5+3


\\ \sf\longmapsto 2x=8


\\ \sf\longmapsto x=(8)/(2)


\\ \sf\longmapsto x=4

User Gaurav K
by
4.6k points
5 votes

Answer: X=4

Explanation:


\Large \boldsymbol {} \sf 1-(2x+4)=-4x+5 \\\\1-2x-4=-4x+5 \\\\4x-2x=5+3 \\\\2x=8 \\\\\boxed{\sf x=4}

User Will Ryan
by
4.7k points